1998
DOI: 10.1097/00004728-199803000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Case Report. Pulmonary Alveolar Microlithiasis: High-Resolution CT and MR Findings

Abstract: We report the high-resolution CT (HRCT) and MR findings in a case of pulmonary alveolar microlithiasis. HRCT revealed that the black pleural line on a chest radiograph was caused not by subpleural cysts but by a fat-dense layer between ribs and the calcified parenchyma. MRI showed both lower zones with diffusely increased signal intensity on T1-weighted images. We speculated it was caused by the accumulation of small-sized calcific particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 9 publications
3
47
0
1
Order By: Relevance
“…Later reports, 7,8 using high-resolution CT (HRCT) scan, suggested that this line was caused by subpleural cysts. Hoshino et al 1 demonstrated that the black pleural line on the chest radiograph corresponded to the fat dense layer between the ribs and calcified parenchyma, and also reported for the first time MRI findings in this case as diffuse calcific micronodules, characterized by an increased signal intensity on T 1 -weighted images, predominantly in the posterior lower zones. There are several reports about findings of PAM on conventional CT and HRCT.…”
Section: Felsonsupporting
confidence: 64%
“…Later reports, 7,8 using high-resolution CT (HRCT) scan, suggested that this line was caused by subpleural cysts. Hoshino et al 1 demonstrated that the black pleural line on the chest radiograph corresponded to the fat dense layer between the ribs and calcified parenchyma, and also reported for the first time MRI findings in this case as diffuse calcific micronodules, characterized by an increased signal intensity on T 1 -weighted images, predominantly in the posterior lower zones. There are several reports about findings of PAM on conventional CT and HRCT.…”
Section: Felsonsupporting
confidence: 64%
“…Hos hi no et al de mons tra ted that the black ple u ral li ne on the chest ra di og raph cor res pon ded to the fat den se la yer bet we en the ribs and cal ci fied pa rench yma. 16 Ho we ver, we think this sug ges tion is not va lid for all PAM ca ses. We de tec ted black ple u ral li ne in chest X-ray of ca se 1 ha ving 5-6 mm subp le u ral cysts.…”
Section: Fi Gu Rementioning
confidence: 87%
“…Hi de a ki et al repor ted that trans lu cent zo nes ca u sed by subp le u ral cysts sho uld be cal led by anot her na me and sho uld be dis tin gu is hed from the li ne that Fel son ori gi nally men ti o ned. 17 The ad van ta ges of high-re so lu ti on CT in detec ting mi ni mal struc tu ral chan ges in the lung parench yma ha ve be en re por ted pre vi o usly. 18,19 High-re so lu ti on CT scans show that the re is a gradi ent of dis tri bu ti on of the cal ci fi ca ti ons in which lung ba ses, es pe ci ally pos te ri or are mo re in vol ved more than the midd le and up per lung zo nes.…”
Section: Fi Gu Rementioning
confidence: 99%
“…Multiple pulmonary nodular calcifi cations on chest X-ray and CT are a pathognomonic fi nding of PAM, and diffuse and intense tracer uptake in both lungs on bone scintigraphy is widely known [2][3][4]. To the best of our knowledge, there have been no reports on FDG uptake by the lung in cases of PAM.…”
Section: Discussionmentioning
confidence: 99%
“…Although computed tomography (CT) and bone scintigraphic fi ndings of PAM have been reported earlier, the uptakes of 18 F-fl uorodeoxyglucose (FDG) in FDG-positron emission tomography (PET)/CT in lung are not yet known [2][3][4]. FDG-PET has come to be recognized as a useful tumor imaging technique on the basis of the elevated glucose metabolism in tumor cells.…”
Section: Introductionmentioning
confidence: 99%